A census of the nearby Pisces-Eridanus stellar stream: commonalities with and disparities from the Pleiades - Röser, Siegfried; Schilbach, Elena (Astronomy and astrophysics, 2020)
Aims.Within a sphere of 400 pc radius around the Sun, we aim to search for members of the Pisces-Eridanus (Psc-Eri) stellar stream in the Data Release 2 data set. We compare basic astrophysical characteristics of the stream with those of the Pleiades Methods. We used a modified convergent-point method to identify stars with 2D velocities consistent with the space velocity of the Psc-Eri stream and the Pleiades, respectively.Results. In a G magnitude range from 5.1 mag to 19.3 mag, we found 1387 members of the Psc-Eri stream at distances between 80 and 380 pc from the Sun. The stream has a nearly cylindrical shape with a length of at least 700 pc and a thickness of 100 pc. The accumulated stellar mass of the 1387 members amounts to about 770 M⊙, and the stream is gravitationally unbound. For the stream, we found an age of about 135 Myr. In many astrophysical properties, Psc-Eri is comparable to the open cluster M45 (the Pleiades): in its age, its luminosity function, its present-day mass function, as well as in its total mass. Nonetheless, the two stellar ensembles are completely different in their physical appearance. We cautiously give two possible explanations for this disagreement: (i) the star formation efficiency in their parental molecular clouds was higher for the Pleiades than for Psc-Eri, and/or (ii) the Pleiades had a higher primordial mass segregation immediately after the expulsion of the molecular gas of the parental cloud.
Gesehen am 13.07.2020